Discurso: em busca da essência do pensamento de Émile Benveniste - Almeida, Natália Cristina de (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation investigates the notion of discourse in Émile Benveniste’s work. Starting from Gérard Dessons’s statement (2006), which says that Benveniste is the "inventor of discourse", this study aims to elucidate the place occupied by this concept in the benvenistian work. To do so, we undertake a search for references to Benveniste in the Dictionary of Discourse Analysis (CHARADEAU; MAINGUENEAU, 2008), as well as a discussion of points of his Theory of Enunciation that can lead the reader to an indicialist reading. We expatiate on Benveniste’s path from his affiliation with Saussure, through his overcoming of his master, until his arrival at the concept of language-discourse. This concept is defined in this study as the particular semiotic of each speaker. The effective analysis of the term discourse is performed based on a theoretical corpus delimited from a methodological path of reading. This corpus is composed of nine texts from Problems in General Linguistics I and II: Observations on the functioning of language in the freudian discovery (1956), The nature of pronouns (1956), Subjectivity in language (1958), A look at the development of linguistics (1963), The levels of linguistic analysis (1964), Language and human experience (1965), Form and meaning in language 1966), The semiology of language (1969), and The formal apparatus of enunciation (1970). From the analysis of these texts, we establish an inseparable relationship between enunciation and discourse: they are interdependent, but distinct. The analysis reveals that when the speakers appropriate language-discourse, they remove it from the state of possibility, actualizing it, converting it into discourse by the act of enunciation, ie, (inter)subjectively implying themselves. Therefore, discourse is defined as the manifestation of enunciation, responsible for promoting human experience, which only finds fulfillment in and through language.
Keywords: Discurso; Língua-discurso; Teoria da Enunciação de Émile Benveniste; Discourse; Language-discourse; Émile Benveniste’s theory of Enunciation; ACCNPQ::Lingüística, Letras e Artes::Lingüística